A Case of Wegener’s Granulomatosis Presenting with Unilateral Facial Nerve Palsy - Roy Ujjawal; Pan Koushik; Panwar Ajay; Chakrabarti Subrata (Case Reports in Medicine)
Wegener’s granulomatosis or granulomatosis with polyangiitis is a necrotizing vasculitis affecting both arterioles and venules. The disease is characterized by the classical triad involving acute inflammation of the upper and lower respiratory tracts with renal involvement. However, the disease pathology can affect any organ system. This case presents Wegener’s granulomatosis presenting with facial nerve palsy as the first manifestation of the disease, which is rarely reported in medical literature.